MEDICAL RECORD APPLICATION WITH MOBILE WEB-BASED BARCODE SYSTEM - Sutejo Sutejo; Angger Purno Nugroho; Mei Sartika; Irshal Wahyu Pratama (Jurnal TAM (Technology Acceptance Model), 2021)
Medical record is a file containing notes and documents regarding patient identity, examination, treatment, actions, and other services to patients at health care facilities. According to the Regulation of the Minister of Health of the Republic of Indonesia in 2008 in Article 1, medical records are files containing notes and documents regarding patient identity, examination, treatment, actions, and other services which have been provided to patients. In the development of the medical record system, the waterfall method is used which is a method which takes a systematic approach from the level of system requirements to the analysis, design, coding, testing, and maintenance stages. Many methods are used in system development such as the prototyping method, waterfall, and others. In this study, only the waterfall development method is used because each stage will be carried out sequentially from System Design, System Analysis, Coding, System Implementation, and System Maintenance. Based on the results of the study of research progress, analysis, design, and implementation of the design of a mobile web-based barcode medical record system at Bhakti Keluarga Husada Clinic, it can be concluded that the system design was carried out using the PHP programming language, MySQL database processing, and the application of a web mobile-based barcode medical record system at Bhakti Keluarga Husada Clinic.